Slowing the loss of physical function in amyotrophic lateral sclerosis with edaravone: Post hoc analysis of ALSFRS‐R item scores in pivotal study MCI186‐19. Issue 2 (10th December 2021) - Brooks, Benjamin Rix; Pioro, Erik P.; Katz, Jonathan; Takahashi, Fumihiro; Takei, Koji; Zhang, Jeffrey; Apple, Stephen
Abstract: Introduction: Phase 3 study MCI186‐19 demonstrated less loss of physical function with edaravone versus placebo, as measured by the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS‐R) total score. A 1‐point drop in an individual ALSFRS‐R item may be clinically meaningful. We assessed ALSFRS‐R item score changes to identify clinical features protected by edaravone treatment. Methods: Time‐to‐event analysis was used to assess the cumulative probabilities of reductions in ALSFRS‐R item scores and Amyotrophic Lateral Sclerosis Assessment Questionnaire (ALSAQ‐40) subdomain scores. Results: Edaravone use was accompanied by: (1) delayed drop of ≥1 point in ALSFRS‐R item score for four items: salivation, walking, climbing stairs, orthopnea (unadjusted), or for two items: walking, climbing stairs (after Bonferroni correction for multiple comparisons); (2) delayed score transition from 4 or 3 at baseline to ≤2 for five items: swallowing, eating motion, walking, climbing stairs, orthopnea (unadjusted), or for one item: climbing stairs (after Bonferroni correction for multiple comparisons); and (3) delayed worsening of ALSAQ‐40 domain scores representing daily living/independence, eating and drinking (unadjusted). Discussion: These post‐hoc analyses identified the ALSFRS‐R item scores and ALSAQ‐40 domain scores that were associated with preserved gross motor function and health‐related quality of life, respectively, after edaravone treatment. Limitations of post‐hoc analyses should be considered when interpreting these results. We recommend that clinical trials employing the ALSFRS‐R include this type of analysis as a pre‐specified secondary outcome measure.